Interior Design and Furniture of Office Buildings for " Physically Handicapped " - Nardine El-Shaefaey; saeed Hassan Abd Elrahman; PROF.DR./NOHA F. IBRAHIM (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2023)
The conditions of individuals who suffer from some disorder in their mobility or ‎‏‎ activity influence their social and emotional development. The percentage of ‎‏mobility disability varies from one society to another according to a number of factors, the most important of which are genetic ‎‏‎, health and cultural awareness factors and the criteria used to define each ‎‏‎ manifestation of motor impairment‏More recently, in most countries of the world, the number of ‎people with special ‎‏‎ needs has increased in comparison with the population ‎‏As a result of the occurrence of many demographic changes in life and the spread of ‎‏health factors affecting pregnant women before and during childbirth, which cause disabilities, there has been ‎‏‎ great interest in groups with special needs at all levels, and ‎‏‎ their proportions have grown worldwide as follows‏ ‎‏‎‎‏80%‏‎ ‎‏‎‎ people with special needs are mostly from third world‎ ‎‏‎ developing countries‎‎ ‎‏15%‏‎ of the world's population with special needs.‎‏ At the beginning of the ‎‏21‏st century, the projected share will be ‎‏13.5%‏‎ of ‎‏total world population ‎‏